2017
DOI: 10.1007/s40501-017-0102-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Management of Anxiety Disorders in the Elderly

Abstract: Opinion Statement Anxiety disorders are common in the elderly. Additionally, anxiety symptoms often accompany co-morbid psychiatric, medical, as well as neurodegenerative diseases in the older population. Anxiety in the elderly, often accompanied by depression, can lead to worsening physical, cognitive and functional impairments in this vulnerable population. Antidepressants are considered first line treatment. Both SSRIs and SNRIs are efficacious and well-tolerated in the elderly. Some SSRIs are strong inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 74 publications
(76 reference statements)
2
19
0
4
Order By: Relevance
“…This explained why we found that maternally separated treated rats spent more time in the open arms of the EPM than nonseparated treated (NSF) rats. The long-term treatment with Fluvoxamine produced noticeable behavioral relief in agreement with previous studies that showed that psychological disorders including anxiety and depression are relieved with prolonged and consistent antidepressant treatment [27,64]. Fluvoxamine may have activated the HPA axis resulting in neuroendocrine responses via specific serotonergic neurons [65].…”
Section: Discussionsupporting
confidence: 87%
“…This explained why we found that maternally separated treated rats spent more time in the open arms of the EPM than nonseparated treated (NSF) rats. The long-term treatment with Fluvoxamine produced noticeable behavioral relief in agreement with previous studies that showed that psychological disorders including anxiety and depression are relieved with prolonged and consistent antidepressant treatment [27,64]. Fluvoxamine may have activated the HPA axis resulting in neuroendocrine responses via specific serotonergic neurons [65].…”
Section: Discussionsupporting
confidence: 87%
“…One of the reasons behind it is the fact that beta blockers such as metoprolol and propranolol are lipophilic and can cross the bloodbrain barrier [84]. Lipophilic adrenolytic drugs are also metabolized by the liver, which is an important aspect as far as elderly patients affected by heart or liver diseases are concerned [85]. Moreover, there is a number of other psychoactive drugs which can influence the effectiveness of beta blockers and their side effects.…”
Section: Risk Factors Related To Using Adrenolytic Drugs In the Pharmmentioning
confidence: 99%
“…Drugs from the SSRI group may increase the concentration of beta-adrenolytic drugs in blood plasma. However, tricyclic antidepressants can increase their antihypertensive effect [85]. For this reason, beta blockers are not recommended to be used in anxiety disorders in geriatric patients.…”
Section: Risk Factors Related To Using Adrenolytic Drugs In the Pharmmentioning
confidence: 99%
See 2 more Smart Citations